Post-Traumatic Left Subclavian Artery Pseudoaneurysm Secondary to Clavicular Fracture: A Case Report and Literature Review - Małgorzata Edyta Wojtyś; Patryk Skórka; Dawid Kordykiewicz; Aleksander Falkowski; Joanna Jakubowska-Grzeszyk; Janusz Wójcik; Edward Michael Wojtys (Biomedicines)
Subclavian artery pseudoaneurysms are rare but potentially life-threatening vascular injuries frequently associated with trauma such as clavicle fractures. In this paper we describe the case of a 49-year-old male who developed a post-traumatic pseudoaneurysm of the subclavian artery after a bicycle accident. The diagnosis was delayed due to non-specific symptoms and an initially missed aneurysm on computed tomography imaging. Persistent pain, swelling, and erythema in the subclavian region prompted further detailed diagnostics, which ultimately revealed the pseudoaneurysm. The patient was successfully treated with endovascular stent–graft implantation. We screened the PubMed database to identify similar cases managed exclusively through endovascular intervention. Reports of iatrogenic pseudoaneurysms and those treated with open surgery were excluded. Variables such as time to diagnosis, clinical presentation, features of pseudoaneurysms, and complications were analyzed to highlight the role of endovascular techniques as a minimally invasive and effective treatment option. These cases pose both a diagnostic and a therapeutic challenge, as early recognition of symptoms is crucial to prevent serious complications including thrombosis, neurological deficits, and even limb loss.